Online Continuing Professional Development: Discourse Analysis of Primary Teachers’ perspectives on Visual Arts Appreciation at Primary Level. - Flannery, Michael (Faculty of Education, The National College of Art and Design, A Recognised College of the National University of Ireland, 2020)
Online continuing professional development courses have been a highly popular choice in recent years with Irish primary teachers. For the researcher, computer-mediated communications from a virtual learning community can provide a rich pool of data. This thesis documents some of the opportunities and obstacles encountered in using primary teachers’ online discourse hosted within the learning management system Moodle to generate theory in order to explain current implementation of visual arts awareness, appreciation and appraisal at primary level. This study investigates why, according to recent national research, visual art appreciation and appraisal (looking and responding) has not translated well from the curriculum documents into classroom practice. It examines why looking and responding has not been embraced as readily as other components since the curriculum’s introduction in 1999. It explores why teachers tend to address a narrow spectrum of visual art despite their current mindfulness of diversity in the classroom and inclusive practice. This research has adopted a discourse analysis method of enquiry and a grounded theory approach, as theory evolved from data. Data consisted of online reflective learning logs and forum discussion postings volunteered by 2,100 Irish primary teachers over four consecutive summers from 2006 to 2009. Both quantitative and qualitative methods have been applied. The study has an autoethnographic component also, in the format of self-interview, as throughout this inquiry, the researcher fulfilled another role of online course developer. The study suggests Irish primary teachers’ expressionistic epistemological leanings and perceived levels of connoisseurship negatively impacts upon the frequency and quality of visual arts appreciation. It proposes that the integrationist and thematic approaches advocated by the primary curriculum steer primary teachers towards addressing certain kinds of artwork to the neglect of others. Primary teachers’ selection criteria is based more on a work’s perceived potential for integration or general language development, rather than selecting art for art’s sake. This inquiry also suggests that teachers’ personal comfort zones, preferences and lack of confidence limit the resultant art appreciation menu to familiar and narrative works predominantly. There is little challenge provided in terms of semiotics or critical dialogue. An understandable conservatism regarding artwork selection also stems from their position of loco parentis and their mindfulness of the different values held by the various religious or cultural groups they teach. This study also explores the nature and potential of online resource based learning for the continuing professional development of primary teachers in terms of developing their looking and responding classroom practice. It investigates its potential in enabling teachers to reflect on their current looking and responding practice and to clarify their roles and responsibilities in mediating children’s interactions with artwork by other professional artists, craftspeople and designers.
Keywords: Research Subject Categories::HUMANITIES and RELIGION; Primary school teachers; Learning management system; Artwork; Visual arts